Craniosynostosis Following Fetal Methotrexate Exposure. Issue 2 (March 2016) - Zarella, Christopher S.; Albino, Frank P.; Oh, Albert K.; Wood, Benjamin C.; Oluigbo, Chima O.; Myseros, John S.; Magge, Suresh N.; Keating, Robert F.; Rogers, Gary F.
Abstract : Abstract: Methotrexate (MTX) is an antimetabolite, folic acid antagonist that inhibits purine nucleotide production, DNA synthesis, and cellular proliferation. Despite widespread therapeutic uses, MTX remains a potent teratogen. Methotrexate embryopathy encompasses multiorgan system dysfunction, including intrauterine growth restriction as well as cardiac, craniofacial, renal, genital, and skeletal abnormalities. Effects of MTX exposure on fetal development continue to be described. This series of 4 patients with MTX-associated craniosynostosis represents the largest published association between prenatal MTX exposure and premature cranial suture closure.